PENGARUH PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KECENDERUNGAN PRAKTEK KECURANGAN - Novi Akhsani (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
This study aimed to analyze the influence of internal control (PI), Compensation Compliance (KK) and Organizational Culture (BO) to Tendency of Fraud Practices (PK) in Electricity Company incorporated in the Association of Indonesian Electricity Contractors, especially DKI Jakarta. Through good internal control is expected to reduce the action to commit fraud. Data collection techniques through survey using primary data. Data processing using SPSS software version 20. The results showed that simultaneously Internal Control variables (PI), Compensation Compliance (KOM) and Organization Culture (BO) have a significant effect on Tendency of Fraud Practices (PK). Coefficient of Determination (R2 ) shows the number of Adj R 0.352 which means 35.2% dependent (Y) Tendency of Fraud Practices (PK) influenced by three independent factors (X) while the rest of 64.8% is influenced by other variables.